Associations between Recession hardships and subjective and objective sleep measures in the midlife in the United States study: race and gender differences - Bhat, Aarti C.; Diaz, Jose A.; Lee, Sun Ah; Almeida, David M.; Lee, Soomi (Frontiers in Sleep, 2024)
Objectives: This study investigates the associations of retrospective reports of Recession hardships with 10-year changes in subjective and objective indicators of sleep, and whether these associations differ by race and gender.Methods: 501 adults (14.57% Black; 54.49% female) from the Midlife in the United States (MIDUS) study reported on the subjective Pittsburgh Sleep Quality Index (PSQI) across two waves (pre-Recession, collected 2004-2009; post-Recession, collected 2017-2022), as well as Recession hardships since 2008. A sub-sample of 201 adults (25.37% Black; 58.21% female) provided objective actigraphy-measured sleep data (total sleep time, sleep onset latency, sleep efficiency) across the two waves.Results: Descriptive analyses revealed Black participants had higher average Recession hardships, poorer post-Recession PSQI scores, and poorer post-Recession actigraphy sleep quantity and quality compared to white participants. Females had higher average Recession hardships compared to males; and reported poorer post-Recession PSQI, but had better objective post-Recession sleep quantity and quality compared to males. Regression models showed Recession hardships (across overall events, and sub-domains of financial and housing hardships) were associated with poorer PSQI and actigraphy-measured sleep efficiency following the Recession, adjusting for sociodemographic covariates, corresponding pre-Recession sleep variables, and pre-Recession chronic conditions. There was no evidence for significant moderation by race on sleep outcomes. However, gender moderation indicated associations between housing hardships and poorer actigraphy-measured sleep efficiency were more apparent for females than for males.Findings indicate that Recession hardships (particularly in financial and housing domains) may be manifested in poor sleep. Racial and gender groups may have differential exposure and sleep-related reactivity to Recession hardships.